Upaya Meningkatkan Hasil Belajar PKN Melalui Model Pembelajaran Teams Games Tournament di Kelas IV SDN 173/X Lambur II - Kahar Kahar (Universitas Batanghari Jambi, 2022)
This study aims to obtain information and discuss efforts to improve PKN learning outcomes through the Teams Games Tournament learning model in class IV SDN 173/X Lambur II. This type of research is classroom action research. This research was carried out from July to August in the odd semester of the 2021/2022 academic year for the fourth grade students of SDN 173/X Lambur II. The research subjects were the fourth grade students of SDN 173/X Lambur II, totaling 29 students. Data collection tools in the form of test sheets, observation sheets and documentation. The data analysis technique is in the form of a percentage. This research uses two cycles, starting from planning, implementing, observing, and reflecting. The results of data analysis show that by applying the Teams Games Tournament type learning model using the act of giving gifts, it can improve PKN learning outcomes in class IV SDN 173/X Lambur II.